1993
DOI: 10.1128/iai.61.5.1950-1957.1993
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mixtures of purified Haemophilus influenzae outer membrane proteins in protection against challenge with nontypeable H. influenzae in the chinchilla otitis media model

Abstract: Nontypeable Haemophilus influenzae (NTHi) is one of the leading causative agents of bacterial otitis media, and no vaccine has been shown to be effective against it. Three outer membrane lipoproteins of NTHi have been investigated extensively and are leading candidates for inclusion in a vaccine against this organism. Hi-PAL (P6), recombinant PCP (rPCP), and e (P4) proteins are antigenically conserved among NTHi strains and elicit bactericidal and protective antibodies. A genetic fusion of the rPCP and Hi-PAL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 33 publications
1
40
1
Order By: Relevance
“…1A). In order to analyze whether expression of Omp18 in these plasmids was promoted by the vector, the ⍀-Spc fragment, which contains a strong transcription stop signal (7), was inserted between the p lac promoter of the vector and the cloned insert. No difference in the expression of Omp18 was observed in E. coli strains harboring pIVB11 or pIVB12 or the pIVB11:⍀-Spc or pIVB12:⍀-Spc derivatives, respectively, indicating that the gene encoding Omp18 was expressed in E. coli from an endogenous C. jejuni promoter sequence on the cloned fragment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A). In order to analyze whether expression of Omp18 in these plasmids was promoted by the vector, the ⍀-Spc fragment, which contains a strong transcription stop signal (7), was inserted between the p lac promoter of the vector and the cloned insert. No difference in the expression of Omp18 was observed in E. coli strains harboring pIVB11 or pIVB12 or the pIVB11:⍀-Spc or pIVB12:⍀-Spc derivatives, respectively, indicating that the gene encoding Omp18 was expressed in E. coli from an endogenous C. jejuni promoter sequence on the cloned fragment.…”
Section: Resultsmentioning
confidence: 99%
“…Related proteins have been described in a wide variety of bacterial species (6,8,14,17,24,35,38), in which they generally play an important role in the host immune response. In addition, PAL P6 of H. influenzae is suggested to be an important antigen for the induction of protective immunity (7,20). The amino acid sequence of Omp18 shows a consensus sequence for a precursor signal sequence and a cysteine residue at position 19 which is known to be the cleavage site for signal sequence peptidase II (31).…”
Section: Discussionmentioning
confidence: 99%
“…Whole formalin-fixed M. caturrkulis for subcutaneous immunization were prepared according to a modified version of the method described by Green and co-workers (9). In brief, strain 12075 was grown for 4 h in BHI to an O D at 490 nm of 0.5.…”
Section: Bucteriu and Mediamentioning
confidence: 99%
“…This study showed significant differences in the clinical signs of OM between the control and conjugate-immunized groups. Other studies with outer membrane proteins (23) or P6 (13) as immunogens showed no differences between vaccinated animals and controls. Reduction of severity may be due to the neutralization effect of anti-LOS antibodies (IgG) elicited by the dLOS-protein conjugates in the ME cavity since ME inflammation may be induced by endotoxin (LOS) and/or peptidoglycan remaining in the ME after viable bacteria have been eliminated (12,29,42).…”
Section: Discussionmentioning
confidence: 81%